Ways to improve the personnel management system at domestic enterprises (Economics and region, 2021)
Ways to improve the personnel management system at domestic enterprises. The essence of the concept of "personnel management" is clarified in the article. The main tasks of the personnel management system are determined and the characteristic of its main elements is given. The necessity to improve the personnel management system at domestic enterprises is substantiated, as well as the existing main problems are identified. Ways to increase the efficiency of the personnel management system are considered, the main of which is to ensure its automation with the help of specialized software. It is proved that in the conditions of digital economy the urgency of introduction of software products in the personnel management system grows. The main advantages provided by the automation of the personnel management system are given to the enterprises. It is determined that staff is the main asset of any company. The success or failure of the company in the market depends on the proper use of staff. Therefore, the primary task of the enterprise is to ensure the efficient work of staff. This requires an appropriate personnel management system that can select the necessary staff, train them, properly motivate and unleash professional potential for the benefit of the company and the immediate employees. At the same time, as the experience of most domestic enterprises shows, the role of their personnel management system is mainly to perform routine work such as personnel records management. While they do not have enough time for strategically important issues in the field of personnel management. To change the situation, it is recommended to implement the latest achievements of digitalization in the personnel management system, namely specialized software. The latter allows to automate a significant part of the processes of the personnel management system and, accordingly, to increase the efficiency of its operation. Every company should pay important attention to finding ways to improve the efficiency of personnel management. It must be under constant improvement and as automated as possible. Also, domestic companies should study the best European experience in improving the personnel management system and try to implement it by adapting to domestic realities.
Keywords: personnel management system; digitalization; automation of personnel management; software products; personnel